PERENCANAAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KINERJA APARATUR SIPIL NEGARA DI KANTOR KEMENTERIAN AGAMA KOTA JAMBI - Nurhayati Nonong (JENTRE, 2022)
The research aim describes an influence of human resource planning over the civil servants’ performance at Jambi City under The Ministry of Religious Affairs. Primary data obtained were taken from questionnaires of 75 civil servants. The data analysis used quantitative descriptive. The data were processed by using SPSS 25 with simple linear regression analysis. The results showed that the magnitude of influence to human resource planning towards employee performance is 0.420 or 42% and statistically significant (significance of 0.000< α = 0.05). Thus, this article concluded that the human resource planning implemented by The Ministry of Religious Affairs at Jambi City had an effect on improving employee performance.